Clinical Interest of Ambulatory Assessment of Physical Activity and Walking Capacity in Peripheral Artery Disease. Issue 7 (15th July 2015) - de Müllenheim, P.‐Y.; Chaudru, S.; Mahé, G.; Prioux, J.; Le Faucheur, A.
Abstract : The purpose of the present review was to provide, for the first time, a comprehensive analysis and synthesis of the available studies that highlighted the clinical interest of the ambulatory assessment of either physical activity (PA) or walking capacity in patients with lower extremity peripheral artery disease (PAD). We identified 96 related articles published up to March 2015 through a computer‐assisted search of the MEDLINE, EMBASE, and Web of Science databases. Ambulatory‐measured PA or related energy expenditure (EE) in PAD patients was performed in 87 of the 96 included studies. The main clinical interests of these measurements were (a) the assessment of PA/EE pattern; (b) the characterization of walking pattern; and (c) the control of training load during home‐based walking programs. Ambulatory‐measured walking capacity was performed in the remaining studies, using either Global Positioning System receivers or the Peripheral Arterial Disease Holter Control device. Highlighted clinical interests were (a) the assessment of community‐based walking capacity; (b) the use of new outcomes to characterize walking capacity, besides the conventional absolute claudication distance; and (c) the association with the patient's self‐perception of walking capacity. This review also provides for the clinicians step‐by‐step recommendations to specifically assess PA or walking capacity in PAD patients.